REKAYASA SIKLUS PENERIMAAN KAS STUDI KASUS PADA RUMAH SAKIT SWASTA DI SEMARANG - Jaluanto Jaluanto (FEB UNTAG Semarang, 2013)
The purpose of this study is to analyze, to know the advantages and disadvantages of cash collection system in private hospitals in Semarang based on accounting information systems are still running during this time, then reengineered to improve cash collection cycle. Data collection techniques in this study were interviews and documentation. Based on the research, known system of patient care Private Hospital in Semarang, which runs up to now too long because the patient is required to repeatedly (and back) to the Administration outpatients, after the patient completed through the process of health care, and this has resulted in process accounting become too long. Accounting information systems, especially in cash collection in the Private Hospital in Semarang, which is too long results in delays in the process of making financial reports to the Board of Directors. To improve cash collection cycle that has been running for this by making a cash collection system design is shorter in pemprosesannya, namely the patient's payment is made after completing all types of health care in the outpatient clinic at the outpatient administration of the Settlement and a statement made ​​by the Administration patients outpatient care. Design of computerized cash collection system using the method of real time to all processes at the transaction of patients at the Polyclinic and the batch method used in the accounting for all patient care data from the Administration outpatients in the process the next day as a step supervision. The result is expected to be used as a guide in improving the cash collection system that runs so far in the Private Hospital in Semarang.